The Effectiveness of Giving Red Spinning Juice on Increasing Hb Levels for Pregnant Anemia in the Work East Lahewa Health Center Year 2020 - Rumiris Simatupang (Institute of Computer Science (IOCS), 2021)
Iron anemia that occurs during pregnancy is a condition where the Hb level of pregnant women in the first and third trimesters is below 11 gr/dl. The proportion of pregnant women who experienced anemia in 2013 was 37,1% and increased in 2018 to 48,9%.The purpose of this study was to determine the effectiveness of giving red spinach juice in increasing Hb level in anemic pegnant women.This type of research is quantitative with a quasi-experimental approach through one group pre-post test.This research was carried out in the Work Area of the East Lahewa Health Center in November 2020.The population in this research were all 52 pregnant women who were anemic.The sample in this study were 20 Pregnant mothers.The analysis was carried out by statistical testing, namely the paired t-test to identify the effectiveness of giving red spinach juice in increasing the HB content of pregnant women with anemia before and after treatment.The results showed that there was an effect of consuming red spinach juice on the increase in Hb content in pregnant women with a p-value of 0.000.The results of this research are expected to be able to overcome the problem of pregnant mothers anemia with red spinach juice